KONSEP TEOLOGIS DALAM NASKAH CATOR MI’RÃJ “Menakar Islam dan Budaya Nusantara di Madura” - Ibnurrahman, Junaidi (Analisis: Jurnal Studi Keislaman, 2015)
THE   CONCEPT   OF   THEOLOGY   IN   MANUSCRIPT   BY CATOR MI’RÃJ. “Measuring the Moslem and the Culture in Madura”:  The  manuscript  by Cator  Mi’rãj  is the  classic  songs islam Madura. And it was originally in use by the all Wali, where the trustees  at that time preaching and introduced Islam through cultures  and among them  was a song-macapat.  Sunan  Bonang, Sunan Kalijaga, Sunan Giri and Sunan Kudus, and Sunan Muria are the creators  the beginning  of the song-macapat.  This study uses  the  library  research.  By taking  many factors  such  as the extent  of the discussion, the limited time and ability, the author will limit the objects of the research and the study of theological elements  that  contained  in the  manuscript  Cator  Mi’raj.  What value can be retrieved  from the text  from Cator Mi’raj and the theological  concepts  in the text  of the Mi’raj Cator?  Based on the methods  that  have  been  used,  the  concepts  of God in the manuscript of Cator  Mi’raj is revealed,  it is also including  the Universal Theology  of Human Behavior Theology, and Theology Theocentric  and Theology Anthropocentric.